2014
DOI: 10.1128/aac.00779-13
|View full text |Cite
|
Sign up to set email alerts
|

Types and Prevalence of Carbapenem-Resistant Acinetobacter calcoaceticus-Acinetobacter baumannii Complex in Northern Taiwan

Abstract: eThe frequency of the carbapenem-resistant Acinetobacter calcoaceticus-Acinetobacter baumannii (CRACB) complex increases annually in our hospitals. However, the types and prevalence of carbapenemases among isolates still remain unclear. In this study, we identified and collected 672 carbapenem-resistant isolates from a medical center in Northern Taiwan between April and December of 2010. There were 577 genospecies 2 (Acinetobacter baumannii), 79 genospecies 13TU, and 16 genospecies 3 isolates. The isolates had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Carbapenem resistance is high and the clinician is left with very little choice of antibiotics. The only antibiotic that still retains activity is tigecycline, an observation that has also been made by other authors (Golanbar et al, 2011 ; Hsieh et al, 2014 ). In this unit, piperacillin/tazobactum and amikacin are being used as a pre-emptive (first line) therapy for clinically suspected cases of sepsis.…”
Section: Discussionsupporting
confidence: 63%
“…Carbapenem resistance is high and the clinician is left with very little choice of antibiotics. The only antibiotic that still retains activity is tigecycline, an observation that has also been made by other authors (Golanbar et al, 2011 ; Hsieh et al, 2014 ). In this unit, piperacillin/tazobactum and amikacin are being used as a pre-emptive (first line) therapy for clinically suspected cases of sepsis.…”
Section: Discussionsupporting
confidence: 63%
“…Tigecycline is the first member of the glycylcyclines and is considered to be one of the few therapeutic options to treat multidrug-resistant Acinetobacter infections [5,6]. However, previous studies have shown that the tigecycline resistance rate of carbapenem-resistant A. nosocomialis was up to 21.5% in Taiwan [7].…”
Section: Introductionmentioning
confidence: 99%
“…The growth of all four species of bacteria was inhibited by kanamycin at a concentration of 64 μg/mL. Recently, A. baumannii has become a significant opportunistic pathogen of nosocomial infection in Taiwan, especially in ICU [42]. However, the real challenge is the acquisition of MDR in hospital.…”
Section: Antibacterial Activities Of Tmcn-agnpsmentioning
confidence: 99%